Islamic Propagation in Tiktok Algorithm: The Effectiveness of Proselytizing Millennials in The Digital Era - Zulfa Nouruz Zaman; Mohammad Bahrul Ulum; Fitria wahud (Jurnal Ilmiah Syi'ar, 2025)
This study explores the utilization of TikTok as a medium for Islamic preaching in the digital era, focusing on the millennial generation in Indonesia. TikTok, as a popular social media platform with an AI-based algorithm, offers great potential for spreading religious messages creatively and effectively. However, this algorithmic feature also presents challenges, such as the filter bubble, which may limit information diversity and distort the understanding of religious values. Using a qualitative approach and descriptive method, this study analyzes popular Islamic preaching content on TikTok, such as videos uploaded by Habib Husein Ja’far and other Islamic content. Data is collected and analyzed to identify creative strategies in delivering religious messages, audience reception levels, and the impact of content on young people's religious literacy. The study’s findings can provide practical guidance for Islamic content creators in designing relevant, innovative preaching that aligns with Islamic teachings while also enhancing awareness of digital literacy. Thus, this research contributes to developing transformative digital preaching strategies that adapt to technological advancements.